Cosmography and Topography: A Comparison of André Thevet’s "Les Singularités de la France Antarctique" and Jean de Léry’s "Histoire d’un Voyage Faict en la Terre du Brésil" - Nushaj, Driton (Scholarship@Western, 2016)
The works of Thevet and Léry reveal the emergence of ethnographic genres in the 16th century as debates about religion coincided with rediscovered Greek epistemological methods and principles. A spirit of contestation based on Catholic and Huguenot rivalries motivated the two authors to write down their own historicized accounts of their travels to Fort Coligny – a French colonial outpost in Brazil – during the 1550s. Both authors describe the Tupinamba “savages” in two distinct modes of writing: topography and cosmography. I argue that Léry writes a topography of the Tupi following the distinction made by Michel de Montaigne – i.e., he describes an inhabited place with fidelity, precision, and empirical rigour, albeit from a Calvinist moral position. Thevet, by contrast, writes a cosmography that uses analogy, and Catholic and Aristotelian perspectives to reduce Tupi cultural forms to singularities existing within a universal order.